Onion nursery production: A rewarding agri-enterprise for young farmers - Singh, Gurdeep; Sran, Tejpal Singh (Indian Farming, 2026)
Onion has year-round demand making it highly profitable crop. It is an irreplaceable commodity in every Indian kitchen and used in many dishes either raw or cooked. Thus, commercial onion nursery is an excellent business scope. This article entails the process of onion nursery production with economics and risk factors involved in its production. By using quality seeds, drip/microsprinkler irrigation and scientific management, strong and healthy seedlings can be produced. It offers quick returns and is an ideal opportunity for rural youth and marginal farmers.